Telomere-associated genes and telomeric lncRNAs are biomarker candidates in lung squamous cell carcinoma (LUSC) - Storti, Camila Baldin [UNESP] (2020)
In the past decade, research efforts were made to identify molecular biomarkers useful as therapeutic targets in Non-Small Cell Lung Cancer (NSCLC), the most frequent type of lung carcinoma. NSCLC presents different histological subtypes being the most prevalent LUSC (Lung Squamous Cell Cancer) and LUAD (Lung Adenocarcinoma), and only a subset of LUAD patients' present tumors expressing known targetable genetic alterations. Telomeres and its components, including telomerase, the enzyme that replenishes telomeres, have been considered potential cancer biomarkers due to their crucial role in cell proliferation and genome stability. Our study aims to quantify expression changes affecting telomere-associated genes and ncRNAs associated with telomere regulation and maintenance in NSCLC. We first assessed the transcriptome (RNA-Seq) data of NSCLC patients from The Cancer Genome Atlas (TCGA) and then we tested the expression of telomere-associated genes and telomeric ncRNAs (TERC, telomerase RNA component, and TERRA, telomere repeat-containing RNA) in Brazilian NCSLC patient samples by quantitative RT-PCR, using matched normal adjacent tissue samples as the control. We also estimated the mean size of terminal restriction fragments (TRF) of some Brazilian NSCLC patients using telomeric Southern blot. The TCGA analysis identified alterations in the expression profile of TERT and telomere damage repair genes, mainly in the LUSC subtype. The study of Brazilian NSCLC samples by RT-qPCR showed that LUSC and LUAD express high amounts of TERT and that although the mean TRF size of tumor samples was shorter compared to normal cells, telomeres in NSCLC are probably maintained by telomerase. Also, the expression analysis of Brazilian NSCLC samples identified statistically significant alterations in the expression of genes involved with telomere damage repair, as well as in TERC and TERRA, mainly in the LUSC subtype. We, therefore, concluded that telomere maintenance genes are significantly deregulated in NSCLC, representing potential biomarkers in the LUSC subtype.